The Architecture of Anticipation and Novices' Emerging Understandings of the Principal Position: Occupational Sense Making at the Intersection of Individual, Organization, and Institution. Issue 7 (July 2014) - Spillane, James P.; Anderson, Lauren
Background: While teaching and school-level administrative work remain stepping stones in most pathways to the principal's office, these formal experiences—alongside informal or formal apprenticeships—do not immunize newcomers to the struggles of occupational socialization. To the contrary, crossing over to the principal's office represents a sizable shift as newcomers assume a multifaceted job that spans instructional, managerial, and political realms. Purpose: This manuscript explores novice school principals' efforts to make sense of their new occupation immediately following their boundary passage into the principalship. To frame this work, we draw from the literature on occupational and organizational socialization and newcomer sense making. Sense making—with its emphasis on how meanings materialize in situ, thus informing and constraining identity and action—offers a utile lens given the particular challenges that new principals face as they navigate today's pluralistic institutional environment. Design/Data: Data are drawn from a multiple-methods study of newly hired first-time principals in one large urban school district. Specifically, our analysis focuses on interview data collected from a sample of 18 purposefully selected new principals just after they were hired and just prior to the start of their first year on the job. Findings: We find that, contending with a plurality, diversity, and simultaneity of stakeholder expectations, novices' sense making centered on challenges related to organizational legitimacy and organizational integrity; however, the relative prominence of these dual imperatives differed based on the position of principals' schools in the broader institutional field. Depending upon how imperatives interacted in local organizational contexts, novices faced puzzles of different kind and character. For some, localized puzzles called for a kind of institutional work that we term repairing; for others, puzzles called more for (re-)presenting, refining, and/or maintaining. In crafting courses of action, novices drew on institutional logics and metaphors from personal experience, which they used as resources in their efforts to resist exploding out organizationally and personally in response to multiple stakeholders' diverse demands. Doing so, novices constructed occupational selves that were not unitary and that encompassed inconsistencies and contradictions. Conclusions: Our analysis suggests the need to consider principals' socialization as it unfolds in schools as they are situated within the broader institutional landscape. In addition, whereas much of the sense making literature focuses on microprocesses, our analysis attends to how the institutional environment enters sense making. In doing so, it adds to the knowledge base concerning the microfoundations of institutional theory as it plays out in the education field, and it enriches the empirical research base concerning new principals' expectations and experiences in contemporary public schools.